Intermediate purification of CHO‐derived recombinant human Factor IX using hydrophobic interaction membrane‐based chromatography and its comparison to a sulfated resin. Issue 22 (26th September 2017) - Ribeiro, Daniel A.; Passos, Douglas F.; Ferraz, Helen C.; Castilho, Leda R.
Abstract: This work investigated the use of hydrophobic interaction membrane chromatography for intermediate purification of recombinant human Factor IX (rFIX) produced by CHO cells. The first purification step was based on a strong anion exchange monolith, thus forming a purification process fully based on convective media, which allow operation at high flow rates and low pressure drops, as well as modular scale‐up. Although the starting material was challenging (CHO cell culture supernatant harvested at 70% cell viability), the two‐step purification process showed promising results, with a global purification factor of 298, a global recovery of 69%, and DNA and endotoxin levels close to regulatory limits. Final host cell DNA (68.8 ng per dose of 500 IU), endotoxins (60 EU per dose of 500 IU) and activated FIX (FIXa/FIX = 2.33%) were in levels close to those recommended by regulatory authorities. HCP removal was of 99.98%, decreasing from 9 424 358 ppm in the supernatant to a final HCP value of 2071 ppm. The use of a supernatant harvested at higher viability and/or the addition of a third polishing step focusing on HCP removal could allow meeting the desired HCP range of 50–100 ppm, as well as the regulatory requirements for the other critical contaminants.